Pengaruh Perbandingan Oli Udara Terhadap Kinerja Peredam Kejut (Shock Absorber) Bagian Depan Sepeda Motor - Irawan, Sandi; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2017)
Motorcycle shock breaker consist a tube fill with oil. The oil volume determine the shock breaker performance to reduce shock force. This research is aimed to get the effect of oil air ratio due to motorcycle shock breaker performance. The research is done by determine the amplitude and frequency of the vibration which measure by roll paper recording. The oil volume is vary as 60, 70 and 80 ml. The oil pressure is measure with manometer. The pressure data is used to count pressure force based on telescopic cylinder area. The result shows that oil volume has effect due to shock breaker performance. The result also shows that oil volume has effect due to the vibration.